1996
DOI: 10.1074/jbc.271.16.9816
|View full text |Cite
|
Sign up to set email alerts
|

PKN Associates and Phosphorylates the Head-Rod Domain of Neurofilament Protein

Abstract: PKN is a fatty acid-activated serine/threonine kinase that has a catalytic domain highly homologous to that of protein kinase C in the carboxyl terminus and a unique regulatory region in the amino terminus. Recently, we reported that the small GTP-binding protein Rho binds to the amino-terminal region of PKN and activates PKN in a GTP-dependent manner, and we suggested that

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
54
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 76 publications
(54 citation statements)
references
References 66 publications
0
54
0
Order By: Relevance
“…Whatever the protein-tyrosine kinase activated by Cdc42Hs and Rac1, this protein is not responsible for a direct vimentin phosphorylation. In this respect, the Cdc42Hs-and Rac1-dependent vimentin reorganization again differs from the RhoAdependent collapse, because ROK or protein kinase N (PKN), two RhoA effectors, directly phosphorylate vimentin (26,28,44). In addition, Rho kinase inhibition did not modify Cdc42Hs-and Rac1-dependent vimentin collapse, discounting any Rho kinase involvement in this process (data not shown).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Whatever the protein-tyrosine kinase activated by Cdc42Hs and Rac1, this protein is not responsible for a direct vimentin phosphorylation. In this respect, the Cdc42Hs-and Rac1-dependent vimentin reorganization again differs from the RhoAdependent collapse, because ROK or protein kinase N (PKN), two RhoA effectors, directly phosphorylate vimentin (26,28,44). In addition, Rho kinase inhibition did not modify Cdc42Hs-and Rac1-dependent vimentin collapse, discounting any Rho kinase involvement in this process (data not shown).…”
Section: Discussionmentioning
confidence: 92%
“…Cytoplasmic IF disassembled when phos-phorylated by protein kinase A, protein kinase C, calcium calmodulin kinase II (CaMKII), and Cdc2 kinases. Interestingly, protein kinase N (PKN), a protein kinase activated by Rho, associates and phosphorylates a subunit of neuron-specific intermediate filament, NFL (26) and ROK␣ (RhoA-binding kinase ␣) phosphorylates glial fibrillary acidic protein (GFAP) (27) and vimentin (28).…”
mentioning
confidence: 99%
“…[aSS]Methionine-labeled in vitro translation product corresponding to amino acid residues 1-474 of human PKN was prepared as described previously [9]. Expression vector for the N-terminal region of human PKN fused to GST was made by subcloning the cDNA fragment encoding amino acid residues 1-540 of human PKN into pGEX vector (Pharmacia Biotech Inc.).…”
Section: 3 Preparation Of Recombinant Proteands and In Vitro Bindingmentioning
confidence: 99%
“…Unbound proteins were removed by four washes with binding buffer containing 0.2% Nonidet P-40 and 50 mM NaC1, and by two washes with binding buffer. Specifically bound proteins were eluted with binding buffer containing 10 mM reduced glutathione, subjected to SDS-PAGE, and to autoradiography as described previously [9]. Experiments with synthetic peptides were performed using the various concentrations of peptide in 200 lal of the binding mixture.…”
Section: 3 Preparation Of Recombinant Proteands and In Vitro Bindingmentioning
confidence: 99%
“…Since PKN represents broad substrate specificity in vitro (10), PKN function may be regulated by intracellular targeting as well as by specific interaction with its substrates. We previously demonstrated that PKN associates with and phosphorylates intermediate filament proteins in vitro (17,18), which may be physiological substrates for PKN. PKN interacts with the actin cross-linking protein ␣-actinin, but does not efficiently phosphorylate it in vitro (19), suggesting that ␣-actinin serves as a scaffolding protein that targets PKN to specific cytoskeletal substrates.…”
mentioning
confidence: 99%